Ecopoetics and the Mimesis Problem [ Reffering to Slađan Lipovec Poetry ] - Oblučar, Branislav (Poznańskie Studia Slawistyczne, 2022)
The article discusses the topic of poetry, poetic language and mimesis in the context of ecocritical and ecopoetic approach to the study of literature. The first part presents and discusses significant theoretical and critical insights regarding the relationship between poetic language and the environment—from ecophenomenology to insights influenced bypoststructuralism. Based on these more general observations, the second part provides an interpretation of poetry by contemporary Croatian poet Slađan Lipovec, whose poetry features prominently the themes of the natural environment.